Práce speciálního pedagoga ve školním poradenském pracovišti - Čechová, Julie (Univerzita Karlova, Pedagogická fakulta, 2015)
Diplomová práce se týká profese školního speciálního pedagoga na běžné základní škole a jeho fungování ve prospěch žáků s výukovými obtížemi. V teoretické části práce jsou popsány skupiny žáků, s nimiž školní speciální pedagog pracuje, a způsoby práce s nimi, dále možnosti spolupráce s dalšími partnery (pedagogickými pracovníky, odborníky a institucemi mimo školu a rodiči žáků) při podpoře těchto žáků a třístupňový model péče o žáky s rizikovým školním vývojem. Praktická část se formou kvalitativního výzkumu věnuje tomu, jak nahlížejí na svoji profesi sami školní speciální pedagogové působící v základních školách v Praze KLÍČOVÁ SLOVA: Školní speciální pedagog, školní poradenské pracoviště, třístupňový model péče, speciální vzdělávací potřeby, prevence, diagnostika, intervence This thesis concerns the profession of the school special educational advisorr working in a mainstream primary school and his acting in favor of pupils with learning difficulities. The theoretical part describes the group of pupils with whom the school special educational advisor works and possibilities of this work, the cooperation with other partners (teachers, professionals and institutions outside the school and pupils' parents ) in supporting those pupils and the three-stage model of care for pupils at risk in school development. The practical part in the form of qualitative research examines how school special educational advisors acting in primary schools in Prague see themselves in their profession. KEY WORDS: School special educational advisor, school counseling centre, three-stage model of care, special education needs, prevention, diagnostics, intervention Katedra psychologie Pedagogická fakulta Faculty of Education